LOCUS: An environment description language for JASON - Pereira, Ramon Fraga; Magnaguagno, Maurício Cecílio; Meneguzzi, Felipe; Heinsfeld, Anibal Sólon (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2015)
JASON is an AGENTSPEAK interpreter for multi-agent system devel opment, in which agents are described in the AGENTSPEAK language. There fore, we only have to describe the agent behavior, but the environment does not follow this style, it requires a Java description of how the actions and percep tions operate. This choice of implementation guarantees that even complex envi ronments can be created for JASON, but it requires knowledge about both Java and JASON’s Application Programming Interface (API). In this paper we aim to fill the gap between the languages with an AGENTSPEAK-like description of the environment. To overcome this gap we propose LOCUS, a source-to-source compiler which generates a Java description of the environment for JASON, pro viding the user with an easier starting point to create complex environments with a consistent description for both the agents and the environment. The output of LOCUS can be further modified if required, not limiting the user to the features already provided by LOCUS.